Revealing effects of chain scission during ageing of EPDM rubber using relaxation and recovery experiment. (December 2016) - Kömmling, Anja; Jaunich, Matthias; Wolff, Dietmar
Abstract: Both chain scission and crosslinking reactions occur during ageing of EPDM rubber. However, with many conventional polymer analysis methods such as hardness and DMA, it is hardly possible to obtain information about the contribution of each reaction type to the measured data. For example, hardness and Tg both increase during ageing of EPDM, indicating crosslinking during ageing, but it is not clear whether this is partly counterbalanced by chain scission reactions which would lower hardness and Tg . An indication that chain scission reactions probably counteract the hardness or Tg increase by crosslinking is given by Compression Set (CS) measurements. CS exhibits a higher change than hardness or Tg, as CS increases additively through both chain scission and crosslinking reactions. In order to elucidate the share of chain scission reactions in the total degradation, a method testing relaxation and recovery behaviour using DMA equipment was applied. The method revealed the strong influence of chain scissions, leading to more pronounced relaxation and higher residual strain after compression.